Building Democracy and Freedom of Expression by Fighting the Covid-19 Infodemic in the Digital Space Among the Younger Generation in Indonesia - Lestari Nurhajati; Xenia Angelica Wijayanto; Lamria Raya Fitriyani; Dewi Rachmawati (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
A research conducted by Kaspersky in early 2021 showed data in Southeast Asia that the highest percentage of respondents who spread the news without verification were actually in Gen Z (28%), followed by Gen X (21%), and Baby Boomers (19%). Sharing information without verification is very likely to cause the spread of fake news/hoaxes in online media. Indeed, Indonesia pins high hopes on Gen Z (born from 1996-2010) and Gen Y (1980-1995) that are considered part of the upcoming demographic bonus. In various discussions in the digital space, there are also often excuses for using free speech to justify the spread of the Covid-19 hoax in online media. This study aims to discover more about how the role of the younger generation can fight the Covid-19 hoax in the digital space by building democracy and free speech. Hoaxes continuously produced and disseminated by various groups indirectly become part of infodemic production. Even WHO stated that the condition of strengthening infodemics is as dangerous as the current pandemic worldwide. This research uses the method of discourse analysis and social networking analysis (SNA) using big data analysis on Twitter which Gen Z widely use. The results of this study describe  how is the role of the younger generation to fight the Covid-19 hoax and find out who are the primary gatekeepers among young Indonesians in this fight against the Covid-19 hoax.